Point-Of-Care Testing Curriculum and Accreditation for Public Health—Enabling Preparedness, Response, and Higher Standards of Care at Points of Need - Kost, Gerald J.; Zadran, A.; Zadran, L.; Ventura, I. (Frontiers in Public Health, 2019)
Objectives. To discover the status of point-of-care testing (POCT) education in public health schools, to design learning objectives for teaching public health students POCT, to enable public health professionals to perform evidence-based diagnosis and triage directly at points of need, and to improve future standards of care for public health practice. Methods. We surveyed all U.S. schools of public health, colleges of public health, and public health schools accredited by the Council on Education in Public Health (CEPH) and also included accredited public health programs so that all states in the U.S. were represented. We analyzed survey data, public health books, and board certification content. We used PubMed to identify public health curriculum papers. We assessed 2019 CEPH accreditation requirements. We merged knowledge bases of POCT curriculum. We designed a new curriculum to teach public health students and practitioners the principles and practice of POCT. Results. Public health curricula, certification requirements, and textbooks virtually totally neglect POCT instruction. Only one book, Global Point of Care: Strategies for Disasters, Emergencies, and Public Health Resilience, addresses public health issues. Scholarly papers on public health curriculum omit POCT. No courses address POCT in isolation units during quarantine, despite evidence that recent Ebola virus disease cases in he U.S. and elsewhere unequivocally proved the need for POCT. Modular learning objectives were customized for public health students. We documented boot camps, online credentialing, and self-study that can enable public health graduates to garner POCT skills. Conclusions. Enhancing accreditation requirements, academic training, board certification, and field experience will generate future public health professionals more capable of evidence-based medical decision making directly at points of care, including during crises. A POCT-enabled public health workforce can help stop outbreaks. Public health professionals urgently need skills necessary to perform POCT and prepare America and other nations for threats portending significant adverse medical, economic, social, and cultural impact.